Havana. An approach from the visuality of its streets - Rodríguez Aguilar, Jorge Luis (2024)
Havana is an old city that was once modern. For many scholars, cities,like their inhabitants, are born, develop and die. They die when there are no actions that rescue them, preserve them architecturally andmake them live. Visually, our city is dying today. Beyond the purposesof a group of works in the Historic Center, guarded by the memory of the city historian, Havana is much more than that perimeter declared by Unesco, in 1982, a World Heritage Site and a Wonder City, in 2016. Since then, little by little, its lights have gone out in a great sea of darkness, which urgently needs to be restored with a policy that truly reinforces the existing structures before it is too late.